Piecewise Bounded Quadratic Systems in the Plane - Llibre, Jaume; Silva, Clayton Eduardo Lente da [UNESP]; Silva, Paulo Ricardo da [UNESP] (Springer Nature, 2014)
In this paper we study the sliding mode of piecewise bounded quadratic systems in the plane given by a non-smooth vector field Z=(X,Y). Analyzing the singular, crossing and sliding sets, we get the conditions which ensure that any solution, including the sliding one, is bounded.
Keywords: Quadratic systems; non-smooth dynamical systems